Lecture Model of Student Transfer Discussion Method to Increase Student’s Activeness and Learning Outcomes - Suardi, Suardi; Kanji, Hasnah (Journal of Educational Science and Technology (EST), 2018)
The purpose of this research is to improve students' activity and to learn outcomes through the application of lecturing model of student transfer discussion on the basics of sociology program of Sociology Education of FKIP University Muhammadiyah Makassar. This research includes classroom action research. This classroom action research is conducted in two cycles, each cycle is held 4 times. The study was conducted with the number of students of 90 students from class A and B. The instruments of this study were test and observation sheet, and questionnaire. The data of the research are analyzed quantitatively and qualitatively. The result indicates that: (i) Activity and student learning outcomes in cycle I are categorized high with average score 80.65 for class A and 78.70 for class B, but not yet reached the predetermined standard average of 85, the increase in cycle II is already in very high category for class A and class B. (ii) The learning completeness in cycle I of class A has reached completeness of learning result set ie 75, although class B has not reached the student's overall standard, a significant increase in cycle II for class A and class B based on learning outcomes, liveliness and student questionnaires